The Role of a Work Environment in the Insurance Industry : Applied Research in the National Insurance Company (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to determine the impact of the components of the internal control system on the underwriting process in the national insurance company, through studying and analyzing the internal control and formulating a number of questions expressing the problem of this research, which are associated in essence with the possibility of employing the internal control components in raising the performance of the underwriting process in the insurance company  The national research sample, and a questionnaire was also designed, which was considered the main tool for collecting information in this research, and it was distributed to (94) employees in the company, and the process of analyzing the results was carried out through the ready-made statistical programs (AMOS, V24, EXCEL.SPSS.), as the research reached  The existence of a relationship with the effect of the internal control components according to the (COSO) framework in the underwriting process in the research sample company, which played a major role in raising its performance and striving to achieve its desired goals.